1989
DOI: 10.1093/ajcn/50.4.718
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake and vitamin status of healthy French vegetarians and nonvegetarians

Abstract: The status of thiamin, riboflavin, folate, and vitamins B-6, B-12, C, A, D, and E was investigated in 37 middle-aged and healthy French vegetarians by means of a dietary survey and biochemical studies. Values were compared with those of a group of nonvegetarians. Unsatisfactory intakes of vitamin B-6 were observed: vitamin B-6 intake as a percentage of the French Recommended Dietary Allowances was approximately 66% for vegetarians and approximately 58% for nonvegetarians. Vegetarians had a higher mean intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 39 publications
7
51
1
1
Order By: Relevance
“…However it can also be due to absorptive process impairments provoked by gastric atrophy and malabsorption from food, quite frequent in elderly people (Allen, 2008). Strict vegetarianism is also associated with low vitamin B12 intake values (Craig, 2009;Millet, Guilland, Fuchs, & Klepping, 1989). Vitamin B12 deficiency is the main cause of megaloblastic anemia.…”
Section: Vitamin B12 In Meatmentioning
confidence: 99%
“…However it can also be due to absorptive process impairments provoked by gastric atrophy and malabsorption from food, quite frequent in elderly people (Allen, 2008). Strict vegetarianism is also associated with low vitamin B12 intake values (Craig, 2009;Millet, Guilland, Fuchs, & Klepping, 1989). Vitamin B12 deficiency is the main cause of megaloblastic anemia.…”
Section: Vitamin B12 In Meatmentioning
confidence: 99%
“…3,4 Previous studies have shown considerable differences in BMI and nutrient intakes between meat-eaters and vegetarians. [5][6][7] The Oxford cohort of the European Prospective Investigation into Cancer and Nutrition (EPICOxford) intentionally recruited a high proportion of nonmeat-eaters, including a large number of vegans. 8 In this study, we assessed differences in BMI between different diet groups in EPIC-Oxford and evaluated the contribution of major dietary and lifestyle factors to these differences.…”
Section: Introductionmentioning
confidence: 99%
“…When methionine is consumed in excess, Hcy is metabolized by a transsulfuration pathway (conversion from Hcy to cysteine) that requires vitamin B 6 as the essential cofactor. Under conditions of a negative methionine balance, Hcy is primarily disposed via two methionine-conserving pathways.…”
Section: Introductionmentioning
confidence: 99%